Juvenile idiopathic inflammatory myopathies: results of an open single-center retrospective study - M. I. Kaleda; I. P. Nikishina; S. O. Salugina; E. S. Fedorov; S. V. Arsenyeva; A. N. Shapovalenko; T. N. Pachkoria; V. G. Matkava (Современная ревматология, 2022)
Juvenile idiopathic inflammatory myopathies (JIIM) are rare diseases in which the prognosis is largely determined by timely diagnosis, timing of prescription and effectiveness of therapy.Objective: to characterize the clinical phenotypes, the results of paraclinical examination methods, the spectrum of autoantibodies, as well as therapeutic options in patients with JIIM.Patients and methods. The retrospective study included 37 patients with JIIM hospitalized in the pediatric department of the V.A. Nasonova Research Institute of Rheumatology from 2016 to 2020. All patients underwent a standard clinical and laboratory-instrumental examination in accordance with the diagnosis and severity of the condition.Results and discussion. Twenty-three of the 37 JIIM patients had juvenile dermatomyositis (JDM), 1 had polymyositis, and 13 had overlap-myositis (OM). The ratio of boys and girls was 1:1.7. The median age of onset for JDM was 6.9 years, and OM was 11.3 years. All patients had skeletal muscles involvement, dysphagia was detected in 52.2% of cases of JDM and in 15.4% of cases of OM. An increase in the level of creatine phosphokinase at the time of diagnosis was observed in 72.9% of patients, of lactate dehydrogenase – in 81.1%, of alanine aminotransferase - in 67.6%, of aspartate aminotransferase – in 75.7%. Heliotrope rash and/or Gottron's syndrome were observed in 100% of patients with JDM and in 30.8% with OM. Lung involvement was found in 27% of children. The myopathic capillaroscopic changes were present in 95.2% of patients with JDM and 53.8% with OM. Myositis-specific autoantibodies were found in 10.8% of patients with JIIM.All patients received glucocorticoids, 81.0% methotrexate, 18.9% hydroxychloroquine, 8.1% cyclophosphamide, 8.1% cyclosporine, 2.7% mycophenolate mofetil, 2.7% azathioprine, 67.6% - intravenous immunoglobulin. Biologic disease modifying antirheumatic drugs (bDMARDs) were prescribed to 26% of patients with JDM and to all patients with OM (only in 51.3% of cases with JIIM). The median duration of illness before initiation of bDMARDs therapy was 2.25 years. 58.8% of patients were treated with rituximab (RTM), 41.2% with abatacept (ABA). In 1 patient with OM, represented by a combination of systemic lupus erythematosus and JDM, three bDMARDs were used sequentially: ABA, etanercept and RTM. All patients achieved inactive disease status.Conclusion. JDM is the most common phenotype of JIIM, which is characterized by an earlier age of onset, skin involvement that precedes the development of myopathy, and typical capillaroscopic changes. The conclusion was made about the high efficacy and acceptable safety profile of bDMARDs therapy in children with JIIM, with careful monitoring of its tolerability. bDMARDs can be prescribed even in the early stages of the disease in the presence of unfavorable prognostic factors.